Pengaruh Penerapan Enterprise Resource Planning Terhadap Kinerja Supply Chain Management - Arta Rusidarma Putra; Shella Fiolyta (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2018)
This study aims to determine the effect of implementing Enterprise Resource Planning (ERP) on the performance of Supply Chain Management (SCM) at PT Latinusa Tbk. The sample used in this study was 100 respondents using a sampling technique in the form of random sampling. The instrument used to collect data is a list of questionnaires in the form of Likert model scale and arranged based on the constructs of various theories. The analytical model used in this study is Descriptive Analysis, Analysis of Structural Equation Model (SEM) with AMOS programs. The results showed that ERP implementation consisting of operational, tactical and strategic benefits had a significant effect on SCM's performance consisting of internal business, external business, customer service, and in cost management of PT. Latinusa Tbk. This can be interpreted, if the ERP implementation has increased, the performance of SCM will also increase.